Clozapine prescribing barriers in the management of treatment-resistant schizophrenia: A systematic review - Baig, Anum Iqbal; Bazargan-Hejazi, Shahrzad; Ebrahim, Gul; Rodriguez-Lara, Jaziel (Medicine (Baltimore), 2021)
Treatment-resistant schizophrenia is prevalent and difficult to manage, as patients fail multiple antipsychotic trials before being considered as treatment-resistant. Currently clozapine is the only Food and Drug Administration-approved pharmacotherapy for treatment-resistant schizophrenia but remains under-prescribed. The purpose of this study is to investigate recent literature on clozapine in order to identify barriers to prescribing clozapine and categorize the recommended solutions. We conducted a systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Using free text and the medical subject headings, we searched MEDLINE/PubMed electronic bibliographic database from 2017 until 2020. Eligible studies included peer-reviewed English language articles with multiple methodologies aiming to identify clozapine barriers in treatment-resistant schizophrenia. We used search terms combining clozapine AND treatment OR treatment-resistant schizophrenia AND barriers AND prescribing OR prescription OR prescriber. We merged search results in a citation manager software, removed duplicates, and screened the remaining articles based on the study eligibility criteria. We retrieved 123 studies, however, only 10 articles exclusively met the study inclusion criteria for full text review. These studies represented 20 countries; 6 were exclusively conducted in the US. The top barriers delineated by the studies include: providers' lack of knowledge and training (n = 7), concern about side effects (n = 8), and poor adherence (n = 7). All studies described more than 1 barrier. Other barriers included prescriber-perceived barriers (n = 4), administrative barriers (n = 5), and other healthcare systems-related barriers (n = 3). Top recommendations to overcome clozapine prescription barriers included improving prescriber clozapine education/training, utilizing interdisciplinary teams and providing integrated care via clozapine clinics, and simplifying blood test monitoring. Clozapine remains under-prescribed for patients with treatment-resistant schizophrenia due to multiple barriers related to the individual prescriber, system of care, and technology. It is recommended that by improving prescriber knowledge and training, use of integrated care, and use of technology that can enable continuous, real-time blood test monitoring, these barriers may be overcome.